2022
DOI: 10.3390/cells11233908
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model of Estradiol Production from Ultrasound Data for Bovine Ovarian Follicles

Abstract: In this paper, we present a new way to assess the concentration of estradiol (E2) and Insulin Growth Factor-1 (IGF) based on the results from ultrasound scans combined with mathematical models. The IGF1 model is based on the progesterone (P4) concentration, which can be estimated with models calculating P4 level based on the size/volume of corpus luteum (CL) measured during ultrasound scans. At this moment little is known about the underlying reasons for double ovulation and silent heat occurrences. Both of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It has been reported that INH is able to inhibit FSH-induced E 2 production in granulosa cells ( 25 ). E 2 produced by ovarian follicles plays an important role in governing the estrous cycle and has a direct effect on the reproductive capability of cattle ( 26 ). Elevated level of E 2 and low concentration of P 4 can promote the estrus expression, follicle maturation and ovulation ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that INH is able to inhibit FSH-induced E 2 production in granulosa cells ( 25 ). E 2 produced by ovarian follicles plays an important role in governing the estrous cycle and has a direct effect on the reproductive capability of cattle ( 26 ). Elevated level of E 2 and low concentration of P 4 can promote the estrus expression, follicle maturation and ovulation ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that INH is able to inhibit FSH-induced E 2 production in granulosa cells (25). E 2 produced by ovarian follicles plays an important role in governing the estrous cycle and has a direct effect on the reproductive capability of cattle (26).…”
Section: Discussionmentioning
confidence: 99%